R-MAC: Risk-Aware Dynamic MAC Protocol for Vehicular Cooperative Collision Avoidance System. (28th May 2013) - Guo, Weijie; Huang, Liusheng; Chen, Long; Xu, Hongli; Miao, Chenglin
Abstract : The key for cooperative collision avoidance (CCA) systems is the real-time and reliable delivery of safety-related messages among vehicles, which include periodical beacons and risk-triggered warning messages. In this paper, we first design a risk-aware dynamic medium-access control (R-MAC) protocol tailored for vehicular CCA applications. In this protocol, each frame is divided into two parts: TDMA segment for transferring beacons and CSMA segment for delivering warning messages. Then, we propose a stochastic model to predict the average total number of potential collisions in a platoon of vehicles, which determines the size of CSMA segment in the R-MAC protocol meticulously. Monte Carlo simulations validate that our model is reliable and practical. The performance of the R-MAC protocol is verified through theoretical analysis and extensive simulations under different traffic scenes. Simulation results show that R-MAC outperforms the traditional IEEE 802.11p protocol in terms of packets delivery rate and transmission delay, as well as the Jain's fairness index of the medium access between beacons and warning messages.